Prevalence, bacterial profile and factors associated with urinary tract infections among people living with HIV in Africa: a systematic review and meta-analysis - Ambrose Shabohurira; Emmanuel Eilu; Vidya Sankarapandian; Reagan Muhwezi; Danladi Makeri (Discover Public Health)
Abstract Background Globally about 14–20% of people living with human immunodeficiency virus (PLHIV) seek medical attention as a result of urinary tract infections annually. This has caused a big challenge in developing countries due to limited health-care services, poor health service seeking behaviors, and poverty. Understanding the epidemiology of urinary tract infections in PLHIV is key in making targeted interventions towards the control of this cause of morbidity. Objective This systematic review and meta-analysis aim to provide a comprehensive overview of prevalence, bacterial profile and factors associated with Urinary tract infection among HIV patients in Africa. Methods We searched four bibliographic databases Embase, PubMed, Scopus and Google Scholar in April 2024 to identify studies conducted in Africa that reported urinary tract infections among HIV patients. We formulated a search query using the keywords “urinary tract infections”, “prevalence”; “Africa” with Africa expanded to include individual African countries combined using Boolean operators (AND, OR). The identification, selection and inclusion of studies followed the Preferred Reporting Items for Systematic Reviews and Meta-analysis. Results Our review of thirty studies (30) across eleven (11) African countries involved 8603 participants of which 2032 were positive for urinary tract infections. The prevalence of urinary tract infection among PLHIV in Africa is 24% (95%CI [19.00 – 31.00]; I2 = 97% [97.83–98.43%]), and a total of 1783 bacteria were isolated, with Escherichia coli (n = 855) being the dominant isolate. Having a CD4 cell count less than 200 cells/mm3 and being a female living with HIV increases the risk of acquiring a UTI. Conclusion Approximately 1 in 4 PLHIV across Africa is at risk of acquiring UTI. This high prevalence calls for improved clinical management and interventions to mitigate UTI risk among PLHIV. Efforts should focus on enhancing diagnostic capabilities and  improving access to healthcare.